Filipino Multicomponent Intervention to Maintain Cognitive Performance in High-Risk Population (FINOMAIN): Study Protocol for a Cluster Randomized Controlled Trial - Dominguez, Jacqueline; de Guzman, Ma. Fe; Chen, S. H. Annabel; Sano, Mary; Waldemar, Gunhild; Phung, Thien Kieu Thi (Frontiers in Neurology, 2021)
Background: More than half of the people with dementia live in lower-middle income countries (LMIC), yet we lack research and evidence-based knowledge to guide health promotion and prevention strategies for cognitive decline. In the Philippines, the prevalence of mild cognitive impairment (MCI) and cardiovascular risk factors among older persons are high, making this population at high risk for developing dementia. This protocol describes a cluster randomized controlled trial which aims to investigate the efficacy of a multicomponent intervention to maintain cognitive performance among high-risk population. Methods: This is a cluster-randomized, two-arm, single-blind trial of a multicomponent intervention that combines dance called INDAK (Improving Neurocognition through Dance and Kinesthetics), nutrition counseling and vascular risk management. The intervention arm will receive 12 months (1-hour, twice per week) of INDAK and every 3-months nutrition counseling and intensive vascular risk management and monitoring. The control group will receive usual vascular care advice and referral. A total of 605 (20-25 clusters per arm) community-dwelling Filipino older adults aged ≥ 60 years old with MCI will participate in the study and will be assessed at baseline, 6th and 12th month follow-up. The primary outcome is cognitive performance assessed by Alzheimer’s Disease Assessment Scale – Cognitive (ADAS-Cog), Mnemonic Similarity Tasks (MST) and Executive Function Composite (EFC). Secondary outcomes are functional connectivity assessed through brain imaging, and measures of behavioral, functional level and quality of life. Discussion: The study aims to provide scientific evidence on a public health intervention that is contextualized in community setting to reduce dementia risk among older adults with MCI. This model can be an ecological, low-cost, and effective program, thereby conducive to widespread implementation in the Philippines as well as in other low-resource settings with similar public health challenges. The pilot phase was underway with eight villages (clusters), but temporarily interrupted by the pandemic. The full study is anticipated to start after community restrictions are eased.